The short-term effect of nitrogen on freshwater cyanobacteria and cyanotoxins - Le, Kim Thien Nguyen; Maldonado, Juan Francisco Guerra; Nguyen, Thanh-Luan; Goitom, Eyerusalem; Trigui, Hana; Ndiaye, Ndèye Adiara; Terrat, Yves; Shapiro, B. Jesse; Husk, Barry; Zamyadi, Arash; Sauvé, Sébastien; Prévost, Michèle; et al. (Frontiers in Water, 2024)
Toxic cyanobacterial blooms are a worldwide concern. Nutrients are among the numerous factors that trigger cyanobacterial blooms and the production of cyanotoxins. This study aimed to assess the effect of nitrogen on cyanobacteria and cyanotoxins through a short-term mesocosm experiment. To achieve this, mesocosms were installed in situ in two lakes (the Missisquoi Bay of Lake Champlain and Petit-Lac-St-François) and received 700 μg/L of ammonium or 500 μg/L of nitrate. A shift to Microcystis in the mesocosms with nitrogen addition was observed 2 days after the addition in Missisquoi Bay, where nitrogen was more limited than Petit-Lac-St-François based on nutrient ratios. There was a significant increase of extracellular ΣMCs and MC-LR in mesocosms with the addition of ammonium or nitrate after 48 h compared to control mesocosms. Intracellular and extracellular microcystin concentrations were associated with Microcystis. Microcystis presence was associated with ammonium 48 h after N was added at both sites. Therefore, toxin production following sudden nitrogen addition can occur on short time scales relevant to drinking water treatment plant operations. This information will help treatment plant operators better anticipate the arrival of potentially higher concentrations of cyanotoxins.